EFFECT OF pH AND TEMPERATURE ON GROWTH OF Fusarium oxysporum f.sp.vasinfectum - R. ANNADURAI; M. KAMARAJ; B. BALAGURU (The Bioscan, 2025)
The current analysis aids in understanding the effect of pH and temperature in growth of Fusarium oxysporum f. sp. vasinfectum (FOV). This study also focuses on incidences of Fusarium wilt disease in six places of Tamil Nadu. The isolation of the fungus was done using three different media including potato dextrose agar media, Fusarium specific medium and Czapek’s (Dox) broth. The result imparted that the fungus has higher disease incidences in thiruchencodu region 20.50%) and significant effect on the selected parameters. it emphasis that wilt disease of cotton is endemic and causes destruction to the crop. It gives us a reason to adapt to resistant varieties and integrated pest management strategies to efficiently produce disease free cotton to support the economy of our country.